Far-field modelling of THM processes in rock salt formations - Florian Zill; Christian Bert Silbermann; Tobias Meisel; Fabiano Magri; Thomas Nagel (Open Geomechanics, 2025)
Glaciation cycles are one aspect to be considered in assessing the safety of deep geological repository sites for long-term radioactive waste storage. This study examines the impact of time-dependent boundary conditions and thermo-hydro-mechanical (THM) couplings on geological formations under glaciation-induced stresses, pressures and temperature changes.